2014
DOI: 10.1080/02687038.2014.979394
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lexical deficits on narrative disturbances in fluent aphasia

Abstract: Aims: This study aims at investigating micro- and macrolinguistic skills in persons with fluent aphasia. The label “fluent aphasia” applies to different aphasic syndromes characterized by fluent speech with difficulties in lexical retrieval and/or grammatical processing. We hypothesized that their lexical and syntactic (i.e., microlinguistic) difficulties would affect also their narrative (i.e., macrolinguistic) skills. \ud Methods & Procedures: Growing evidence shows that traditional tests may not be sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 38 publications
1
40
1
Order By: Relevance
“…Andreeta and Marini (2015) assessed micro- and macrostructural aspects of discourse in adults with fluent aphasia and age-matched controls. They reported reduced levels of cohesion and coherence were associated with poor sentence formation and reduced levels of informativeness, respectively (Andreetta & Marini, 2015). Alternatively, other factors, such as psychosocial factors not measured here may have contributed to the ability to relay the temporal and causal relationships depicted in picture stimuli for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Andreeta and Marini (2015) assessed micro- and macrostructural aspects of discourse in adults with fluent aphasia and age-matched controls. They reported reduced levels of cohesion and coherence were associated with poor sentence formation and reduced levels of informativeness, respectively (Andreetta & Marini, 2015). Alternatively, other factors, such as psychosocial factors not measured here may have contributed to the ability to relay the temporal and causal relationships depicted in picture stimuli for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The results are more complicated regarding their macro-linguistic abilities (see Andreetta, Cantagallo, & Marini, 2012). For instance, individuals with fluent aphasia might exhibit problems of cohesion and thematic informativeness (Andreetta, 2014) or discourse organization (Kaczmarek, 1984). However, others report that people with LHD maintain macro-linguistic abilities similar to neurotypical individuals (see Pritchard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bastiaanse and Jonkers (1998) found no difference between agrammatic and anomic PWA in their production of either object or action names in isolation. A possible relationship also exists between problems of phonological encoding and fluency: Andreetta and Marini (2015) found that the production of phonological errors (mainly false starts) was negatively correlated the proportion of complete sentences. As noted before, grammatical completeness is one criterion used to differentiate nonfluent from fluent aphasia (Goodglass & Kaplan, 1983; Kertesz, 1982).…”
Section: Introductionmentioning
confidence: 99%